Overview the inquiry learning model: Attitudes, student characters, and student responses what’s the impact? - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Sabila Eka Septi (Intelektual Pustaka Media Utama, 2023)
The purpose of this study was to find the differences and relationships between student responses, student character, and student attitudes towards the inquiry learning model for physics subjects. The contribution given in this study is useful if the student's response to learning is not good then there are problems in the learning taught by the teacher so that the teacher can improve better teaching techniques. This study uses mixed research methods designed with an explanatory design which is a combination of two methods, namely quantitative and qualitative research methods. The results of the t-test and correlation test of student variables, student character, and student responses can be said to be good but need to be improved optimally so that these variables are beneficial to students. The conclusion of this study is that there is a comparison and influence between students, student characters, and student responses at State Senior High School (SMA) 10 Jambi City on the inquiry learning model in physics subjects. The implication of this research is very important, namely the short-term impact of this research is useful and can be used as a benchmark to improve the quality of student responses, student character, and student attitudes, especially at the high school level.